Multi-axis stress sensor characterization and testing platform. (April 2019) - Agcayazi, Talha; Foster, Marc; Kausche, Hannah; Gordon, Max; Bozkurt, Alper
Graphical abstract: Abstract: Multi-axis mechanical stress sensors have become an important tool in numerous fields. To characterize the quality and resolution of a new stress sensor, researchers use test platforms to apply controlled amounts of shear and normal stresses. Since commercially available multi-axis test platforms are expensive, in many cases researchers end up needing to build their own sensor characterization platforms. In this study, we describe a cost-effective multi-axis stress sensor characterization platform to reduce development time, enable accurate benchmarking and provide an open source standard for stress sensor characterization for other researchers. In our design, we combined a 3-axis translational stage and a 3-axis force and torque (F/T) sensor through custom hardware and software. Our platform is cost effective and can reach the limits of the F/T sensor (Fxy = ±65 N and Fz = ±200 N) without losing any accuracy to structural bending. We provide detailed construction and operation instructions as well as results of extensive static and cyclic load experiments. To further validate our system, we show characterization results from a custom stress sensor as a case study. The modular nature of our platform also enables other researchers to customize this characterization platform for their unique experimental requirements.